Assessment of the Multi Functionality of a Small Hydropower Project at Padhu Khola, Kaski, Nepal (Technical Journal, 2020)
Nepal has not utilized the potential of the water resources to the full extent. Systematic and wise development of such resources is of paramount importance for enjoying the maximum possible benefits. This study focused on the needs, challenges, and opportunities of new multifunctional small hydropower projects in Nepal. This study on Padhu Khola shows the possibility of incorporating other facilities along with hydropower for the locality’s socio-economic development. The selection of the best layout of the hydropower generation and distribution of other hydropower components showed that the stream Padhu Khola had a power potential of 1 MW. The economic analysis resulted in the benefit-cost ratio of freshwater aquaculture, drinking water plants to be 1.98 and 1.97 respectively. Other facilities like forestry, local employment facilities, and tourism development were found feasible and practicable.